MARC ANTONY IN THE WORLD OF HELLINISTIC MONARCHIES: SOVEREIGN OR MAGISTRATE? - E. V. Smykov (Гуманитарные и юридические исследования)
The article examines the question whether the political practice of the Hellenistic monarchy had a profound influence on the policy of the Roman triumvir Marc Antony. In search of the answer the numismatic data is referred to - issues of Antony coins, dating back to the time of his stay in the Orient, inscriptions in his honor, data on his religious policy. All this set of materials shows that, in general, Antony remained within the framework of Roman political traditions. There is no reason to talk about his "monarchismi", he was a mere Roman traditionalist like other leaders of the Roman political groups of the time.